PENGARUH KOMPETENSI GURU TERHADAP PRESTASI BELAJAR SISWA ( SURVEI PADA MATA PELAJARAN EKONOMI KELAS XII MA MA’ARIF NU CIMANGGU KABUPATEN CILACAP ): PENGARUH KOMPETENSI GURU TERHADAP PRESTASI BELAJAR SISWA ( SURVEI PADA MATA PELAJARAN EKONOMI KELAS XII MA MA’ARIF NU CIMANGGU KABUPATEN CILACAP ) - Sanusi, Anwar; Sri Lestari; Inngamul Wafi; Yogi Nurfauzi (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The objectives of this study were: 1) To determine the competence of class XII economic teachers at MA Ma'Arif NU Cimanggu, 2) To determine the learning achievement of economic subjects in class XII at MA Ma'Arif NU Cimanggu, 3) To determine the effect of competence teachers towards student achievement in class XII in economic subjects at MA Ma'Arif NU Cimanggu.This type of research used in this research is quantitative research. The method used is a survey method. The techniques used to carry out the analysis using simple regression techniques, From the results of the study, the following conclusions were obtained: (1) The category of economic teacher competence at MA Ma'Arif NU Cimanggu, Cilacap Regency which was in the low category was 2 respondents or 15.4%, in the moderate category as many as 10 respondents or 76.9 % and in the high category as much as 1 respondent or equal to 7.7%. (2) The descriptive results of determining the predicate of the value of the 13 respondents obtained the results: 1 or 7.7% of the students got the very good category, as many as 4 or as much as 30 , 7% of students scored in the good category, as many as 8 or 61.6% of students scored in the sufficient category and there were no students who scored in the poor predicate. (3) There was an influence between the competence of economic teachers on learning achievement in economic subjects with a significance value of 0.000. The regression equation can be written: Y = 28,448 + 1,072X. The R value or the correlation value between variables is 0.469 or 46.9%. Meanwhile, the R Square value of 0.355 implies that the effect of economic teacher competence on learning achievement in economic subjects in class XII MA Ma'arif Cimanggu, Cilacap Regency is 35.5%. Keywords: Teacher Competence, Learning Achievement, Economics Subjects